Sugammadex in antagonism of neuromuscular block in anesthesia: a clinical and economic profile - Sacchi, Viola; Iannazzo, Sergio; Giunta, Francesco (Farmeconomia. Health economics and therapeutic pathways, 2009)
Sugammadex is a modified cyclodextrin which acts by encapsulating and inactivating the neuromuscular blocking agents (NMBAs) rocuronium and vecuronium, used to induce relaxation of skeletal muscles during surgery and to facilitate endotracheal intubation. The procedure of reversal of the block at the end of surgery can influence the time to discharge from the operating room and post-operative residual curarization (PORC) incidence, which is related to an increased rate of adverse respiratory events in the post-anaesthesia care unit. Cholinesterase inhibitors are frequently used to reverse neuromuscular block, but their use is associated with potential cardiovascular and respiratory side-effects. The recommended dose-range for sugammadex is 2-16 mg/kg, depending on the level of block: the dose is approximately 2 mg/kg for reversal of moderate blockade, 4 mg/kg for deep blockade and 16 mg/kg for the immediate reversal of a neuromuscular blockade as early as 3 minutes after 1-1.2 mg/kg of rocuronium. Four pivotal, phase III trials studied sugammadex in routine reversal of moderate, deep neuromuscular block and in the immediate reversal of rocuronium-induced block. In all the cases the drug demonstrated of being significantly more efficient than other reversal strategies, providing a faster reversal than the most used anticholinesterase comparator neostigmine. Sugammadex also appeared to have an acceptable safety profile. Acquisition cost of sugammadex is greater than that of neostigmine, but cost-savings related to the reduced theatre time and to the reduced incidence of PORC episodes can offset it. A Budget Impact analysis in the perspective of the hospital has been conducted for the Italian setting resulting in a total cost-save of 7,420 € for one year of activity. In conclusion, sugammadex appears to be a valuable innovation in anesthesiology. This drug represents a safe and effective alternative to anticholinesterase agents.